ANALISIS KESESUAIAN LAHAN BUDIDAYA TAMBAK DI TELUK PAREPARE, KECAMATAN SUPPA, KABUPATEN PINRANG - Ukkas Hamzah; Asbar Asbar; Rustam Rustam (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2022)
The coastal area in Parepare Bay, Suppa District, Pinrang Regency has biodiversity that can be utilized by humans. This makes it vulnerable to natural damage. The suitability of pond land is the most important thing in shrimp farming to maintain production levels and ensure better development of pond farming businesses. The purpose of this study was to analyze the suitability of the coastal land of Parepare Bay for pond activities. The research was conducted in a qualitative method by collecting data through interviews, observations, and documentation during April to June 2021. The results showed that the use of coastal land in Parepare Bay for pond cultivation is still feasible and appropriate.